Silicon photonic integrated wideband radio frequency self-interference cancellation chip for over-the-air in-band full-duplex communication - Xinxin Su; Meng Chao; Xiuyou Han; Han Liang; Wenfu Zhang; Shuanglin Fu; Weiheng Wang; Mingshan Zhao (Chip)
Compared with the traditional frequency division duplex and time division duplex, the in-band full-duplex (IBFD) technology can double the spectrum utilization efficiency and information transmission rate. However, radio frequency (RF) self-interference remains a key issue to be resolved for the application of IBFD. The photonic RF self-interference cancellation (SIC) scheme is endowed with the advantages of wide bandwidth, high amplitude and time delay tuning precision, and immunity to electromagnetic interference. To meet the requirements of the new generation of mobile terminals and satellite payloads, the photonic RF SIC system is desired to be miniaturized, integrated, and low power consumption. In this study, the integrated photonic RF SIC scheme was proposed and demonstrated on a silicon-based platform. By utilizing the opposite bias points of the on-chip dual Mach-Zehnder modulators, the phase inversion relationship for SIC was realized over a broad frequency band. The time delay structure combining the optically switched waveguide and compact spiral waveguide enables continuous tuning of time over a wide bandwidth. The optical amplitude adjuster provides efficient amplitude control with a large dynamic range. After being packaged with optical, direct current, and RF design, the photonic RF SIC chip exhibits the interference cancellation capabilities across L, S, C, X, Ku, K, and Ka bands. In the S and C bands, a cancellation depth exceeding 20 dB was measured across a bandwidth of 4.8 GHz. An impressive cancellation depth of over 40 dB was achieved within a bandwidth of 80 MHz at a central frequency of 2 GHz. For the application of over-the-air IBFD communication at the newly promulgated center frequency of 6 GHz for 5G communication, the cancellation depth of 21.7 dB was demonstrated in the bandwidth of 100 MHz, and the low-power signals of interest were recovered successfully.